PERANCANGAN APLIKASI RESERVASI FUTSAL (FUTSAL-IN) GUNA MEMPERMUDAH PEMESANAN APLIKASI SECARA ONLINE : DESIGNING A FUTSAL RESERVATION APPLICATION (FUTSAL-IN) TO FACILITATE ONLINE BOOKING APPLICATIONS - M. Gilang Ramadhan; Muhammad Arafah Alif; Muhammad Imran Hidajat H; Putri Nirmala; Nurrahmah Agusnaya; Wahyu Hidayat M (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2025)
The futsal reservation application is an innovative solution to facilitate the online field booking process. This article discusses the design of the Futsal-In application, which aims to simplify and enhance user experience in booking futsal fields efficiently. The design methods used include user needs analysis, user interface (UI) design, and development of a platform-based digital application. The Futsal-In application allows users to easily select the field, time, and desired duration, as well as make online payments. Through this approach, it is hoped that the Futsal-In application can improve efficiency in the futsal field booking process and enhance user satisfaction.